2021
DOI: 10.2478/jolace-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of Chinese students’ perceived barriers to effective intercultural communication

Abstract: Chinese students nowadays have more opportunities to engage in interactions with people from different cultures, but meanwhile, their performance in authentic intercultural communications may be impeded by a variety of barriers. In this study, we qualitatively explored and summarized various types of barriers of intercultural communication as perceived by 40 Chinese students, based on Rozkwitalska’s (2010) model. The findings revealed a series of universal barriers that coincided previous studies (e.g., lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Third, this result is also likely related to personality. Research on Chinese students' perceived barriers to effective intercultural communication (Zhang and Zhou, 2021) found that two major personality-related barriers, including shyness and lack of confidence, influenced the participants' performance in intercultural communication.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this result is also likely related to personality. Research on Chinese students' perceived barriers to effective intercultural communication (Zhang and Zhou, 2021) found that two major personality-related barriers, including shyness and lack of confidence, influenced the participants' performance in intercultural communication.…”
Section: Discussionmentioning
confidence: 99%